CELEBGRAM ENDORSEMENT AND PRODUCT QUALITY, HOW DOES IT INFLUENCE THE INTEREST TO SHOP ONLINE? - Irham Amir; Alma Widiyanti (LPPM Universitas Multi Data Palembang, 2023)
This research aims to determine the effect of the endorsement and product quality on online shopping interest on the cosmetic brand EMINA. By using a descriptive quantitative approach, the sampling technique used is random sampling by distributing questionnaires to 100 millennial generation women in Bogor. This study found the endorsement program and product quality have a positive and significant effect on online shopping interest.